Molecular keypad controlled circuit for Ce(iii) and NO3− ions recognition by μw synthesized silicon-embedded organic luminescent sensor. Issue 64 (29th October 2018) - Kaur, Navpreet; Singh, Gurjaspreet; Singh, Jasbhinder; Singh, Akshpreet; Satija, Pinky; Kaur, Gurpreet; Singh, Jandeep
Abstract : This report demonstrates the mimicking of an electronic circuit diagram towards Ce(iii ) ion sensing response supported by molecular keypads. Abstract : This report demonstrates the mimicking of an electronic circuit diagram towards Ce(iii ) ion sensing response supported by molecular keypads. The probe naphthyl based triazole linked silatrane (NTS) was efficiently synthesized using a series of microwave mediated reactions. The luminescent sensor NTS was explored for the ion sensing response towards Ce(iii ) ions using DMSO and DMSO : H2 O 4 : 1 (v/v) as solvent media, respectively. The role of water in Ce(iii ) ion sensing was detected as 'turn-off' response that contradicts the 'turn-on' with DMSO. Further, the sensing of NO3 − ions by NTS–Ce(iii ) ensemble was associated with blue shift on absorption maxima. These mimicking response studies were sketched as circuit diagrams assisted by molecular keypad behaviour as IMPLICATION output logic gate.